2015
DOI: 10.3389/fenvs.2015.00013
|View full text |Cite
|
Sign up to set email alerts
|

Redox homeostasis in plants under abiotic stress: role of electron carriers, energy metabolism mediators and proteinaceous thiols

Abstract: Contemporaneous presence of both oxidized and reduced forms of electron carriers is mandatory in efficient flux by plant electron transport cascades. This requirement is considered as redox poising that involves the movement of electron from multiple sites in respiratory and photosynthetic electron transport chains to molecular oxygen. This flux triggers the formation of superoxide, consequently give rise to other reactive oxygen species (ROS) under adverse environmental conditions like drought, high, or low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(63 citation statements)
references
References 152 publications
0
60
0
Order By: Relevance
“…ROS such as superoxide radical (O 2 • ⁻), hydroxyl radical ( • OH), and hydrogen peroxide (H 2 O 2 ) are either produced by redox (oxidation–reduction) reactions or they are the active derivative of O 2 . These ROS are permanently generated in chloroplasts, mitochondria, peroxisomes, cytosol, and apoplast and are highly reactive and toxic that can oxidatively damage lipids, proteins, and nucleic acids [2], [3], [4], [5], [6], [7] (Table 1). However, recent studies instead of discussing their toxic nature, have concentrated towards their signaling role in several key physiological processes of plants [7], [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…ROS such as superoxide radical (O 2 • ⁻), hydroxyl radical ( • OH), and hydrogen peroxide (H 2 O 2 ) are either produced by redox (oxidation–reduction) reactions or they are the active derivative of O 2 . These ROS are permanently generated in chloroplasts, mitochondria, peroxisomes, cytosol, and apoplast and are highly reactive and toxic that can oxidatively damage lipids, proteins, and nucleic acids [2], [3], [4], [5], [6], [7] (Table 1). However, recent studies instead of discussing their toxic nature, have concentrated towards their signaling role in several key physiological processes of plants [7], [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ascorbic acid cross‐links glycoproteins and glycolipids together with activation of reduction reactions essential for cell elongation (Sofy, Sharaf, & Fouda, ). Ascorbate acid peroxidase stabilizes electron carriers in electron transport chain and thus useful to enhance photosynthesis under stressed conditions (Kapoor et al., ). Further, ascorbic acid acts as cofactor for violaxanthin de‐epoxidase enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…In case of Macrotyloma uniflorum Apase activity and expression was decreased at increasing concentration of Hg, Cd but increased under Zn stress. It is also reported that in cucumber Zinc (Zn) strongly inhibit the activity of acid phosphatase than Mercury (Hg) similarly As (III) acts as inhibitor of Apase activity in some plants (Kapoor et al, 2015;Naji and Varadahally, 2016). Acid phosphatase activity is also reported to increase in plants under Cd stress (Kapoor et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…It is also reported that in cucumber Zinc (Zn) strongly inhibit the activity of acid phosphatase than Mercury (Hg) similarly As (III) acts as inhibitor of Apase activity in some plants (Kapoor et al, 2015;Naji and Varadahally, 2016). Acid phosphatase activity is also reported to increase in plants under Cd stress (Kapoor et al, 2015). In Sorghum bicolor (L.) under Ni metal stress some isoform of Apase had lost and some new isoform produce that showed that Apase is trying to tolerate Ni stress in sorghum.…”
Section: Discussionmentioning
confidence: 98%